TAMI-52. G-CSF SECRETED BY EPIGENETICALLY REPROGRAMMED MUTANT IDH1 GLIOMA STEM CELLS, REVERSES THE MYELOID CELLS’-MEDIATED IMMUNOSUPPRESSIVE TUMOR MICROENVIRONMENT - Alghamri, Mahmoud (Neuro Oncol, 2020)
Mutation in isocitrate dehydrogenase (mIDH) is the main genetic lesion that defines clinical glioma subtypes and prognosis. This gain of function mutation is associated with the production of the oncometabolite, R-2-hydroxyglutarate, that inhibits α-ketoglutarate dependent enzymes such as TET2 and the Jumonji-C domain containing demethylases. The resultant epigenetic modifications elicit profound effects on the tumor biology and on the glioma-infiltrating immune cells. Here, we report that in genetically engineered mouse glioma models(1), IDH1 mutation caused an expansion of tumor infiltration granulocytes. Upon phenotypic and functional characterization, we uncovered that granulocytes in mIDH1 glioma express low level of immunosuppressive molecules and did not inhibit T-cell function. Single-cell sequencing revealed that these granulocytes are heterogeneous and composed of three distinct populations; neutrophils, pre-neutrophils, and a small fraction of immunosuppressive PMN-MDSCs. Moreover, primary human gliomas showed a higher cellular fraction exhibiting the PMN-MDSCs gene signature in wtIDH1 tumors than the mIDH1 tumors. The mechanism by which mIDH1 mediates non-immune suppressive granulocytes expansion involves epigenetic reprogramming which leads to enhanced expression of granulocyte colony-stimulating factor (G-CSF) in stem-like cells. High G-CSF gene expression is correlated with favorable patient outcome solely in LGG-astrocytoma with mIDH1. Thus, G-CSF represents a potential therapeutic that can be harnessed to improve immunotherapeutic responses in wild type IDH1 glioma patients.